2019
DOI: 10.1159/000502082
|View full text |Cite
|
Sign up to set email alerts
|

High-Flux versus High-Retention-Onset Membranes: In vivo Small and Middle Molecules Kinetics in Convective Dialysis Modalities

Abstract: Background: Patients undergoing maintenance hemodialysis (HD) exhibit increased levels of uremic toxins, which are associated with poor outcomes. Recently, new dialysis membranes have allowed clearance of solutes with higher molecular weight, without significant albumin losses high-retention-onset-HD (HRO-HD). Methods: Prospective crossover trial, in which 16 prevalent patients switched from high-flux HD (HF-HD) to online hemodiafiltration (olHDF) and HRO-HD for 4 weeks. The following variables were evaluated:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…22 In our patients, there were no reductions in β2-microglobulin (11.8 kDa) and myoglobin (17 kDa) during MCO phase. In contrast to our results, two studies 23,30 showed that the predialysis concentrations of β2-microglobulin were lower in MCO-HD than in HF-HD. In agreement with these data, in our cohort there was an increment in β2-microglobulin after returning to HF-HD.…”
Section: Secondary Endpointscontrasting
confidence: 99%
“…22 In our patients, there were no reductions in β2-microglobulin (11.8 kDa) and myoglobin (17 kDa) during MCO phase. In contrast to our results, two studies 23,30 showed that the predialysis concentrations of β2-microglobulin were lower in MCO-HD than in HF-HD. In agreement with these data, in our cohort there was an increment in β2-microglobulin after returning to HF-HD.…”
Section: Secondary Endpointscontrasting
confidence: 99%
“…A randomized controlled clinical trial conducted by Weiner in 21 centers in the United States recruited 172 participants and found maintenance of serum albumin levels following treatment with the Theranova 400 dialyzer, with superior removal of larger middle molecules compared with a similarly sized high-flux dialyzer [ 52 ]. Similar results were also found in other small preliminary clinical studies [ 62 , 68 , 108 , 109 ].…”
Section: Safety Concernssupporting
confidence: 91%
“…Figure 1 shows study selection details. We included 26 studies in this review of biomarkers, 15-40 excluding 5 reports of exclusively clinical outcomes. 41-45 Groupings of related citations are in Appendix D.…”
Section: Resultsmentioning
confidence: 99%